Srečko Kosovel and his Hybrid Form of (Constructivist) Diaries - Toporišič, Tomaž (Slavia Centralis, 2024)
The article focuses on the phenomenon of the diaries of the Slovenian avantgarde poet Srečko Kosovel, juxtaposing them with the diary entries of his contemporary F. T. Marinetti. Compared to Marinetti’s highly political and extrovert diaries about the birth of fascism, Kosovel’s diary is very intimate, conceptual, and lyrical. It comments the political life, but in a highly specific manner combining poetry, essays and other literary forms. Kosovel’s diaries thus represent an unexplored segment of 20th-century diaries, belonging to a specific avant-garde genre of diary writing, functioning as chronicles of introspection, while also producing an exceptionally original combination of personal and collective memory.